Development of a nested PCR assay for specific detection of Metschnikowia bicuspidata infecting Eriocheir sinensis - Bao, Jie; Chen, Ye; Xing, Yuenan; Feng, Chengcheng; Hu, Qingbiao; Li, Xiaodong; Jiang, Hongbo (Frontiers in Cellular and Infection Microbiology, 2022)
In recent years, the “milky disease” caused by Metschnikowia bicuspidata has seriously affected the Eriocheir sinensis culture industry. Discovering and blocking the transmission route has become the key to controlling this disease. The existing polymerase chain reaction (PCR) detection technology for M. bicuspidata uses the ribosomal DNA (rDNA) sequence, but low sensitivity and specificity lead to frequent false detections. We developed a highly specific and sensitive nested PCR method to detect M. bicuspidata, by targeting the hyphally regulated cell wall protein (HYR) gene. This nested HYR-PCR produced a single clear band, showed no cross-reaction with other pathogens, and was superior to rDNA-PCR in specificity and sensitivity. The sensitivity of nested HYR-PCR (6.10 × 101 copies/μL) was greater than those of the large subunit ribosomal RNA gene (LSU rRNA; 6.03 × 104 copies/μL) and internal transcribed spacer (ITS; 6.74 × 105 copies/μL) PCRs. The nested HYR-PCR also showed a higher positivity rate (71.1%) than those obtained with LSU rRNA (16.7%) and ITS rDNA (24.4%). In conclusion, we developed a new nested HYR-PCR method for the specific and sensitive detection of M. bicuspidata infection. This will help to elucidate the transmission route of M. bicuspidata and to design effective management and control measures for M. bicuspidata disease.